2 Old Assumptions, New Work - Ashford, Susan J.; George, Elizabeth; Blatt, Ruth (Academy of Management Annals, 2007)
We review the literature on nonstandard work with three aims: to portray the breadth and nature of the research and theorizing to date, to document the challenges and opportunities this domain poses to both practice and theory, and to bring the study of nonstandard work more to the center stage of micro-OB. After defining nonstandard work and documenting scholarly interest in it, we discuss the literature on the experience of nonstandard workers, on managing the nonstandard workforce, as well as that on managing the interface between standard and nonstandard workers. We analyze the themes that are raised in these literatures and point to new research questions that need to be addressed. Research on nonstandard work can enhance our understanding of the nature of work, the relationship between individuals and organizations, and how organizations and individuals can undertake these new work forms.